Leader transparency and self-awareness predict employee state mindfulness: a literature review - Hellya Agustina,; Nur Atiqah Abdullah @ Janette Marcial,; Rasidah Arshad,; Ahmad Raflis Che Omar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Enhancing employee mindfulness in an organisation setting necessitates the presence of transparency and self awareness. Through the transparency and self-awareness, it has the potential to be nurtured and refined through the passage of time, and they have significant importance in successfully inspiring and driving employees towards the objectives of the organisation. Furthermore, it is important to note that leaders can modify their leadership approach based on different situations and the unique characteristics of individuals. The versatility can significantly improve effectiveness in managing diverse teams and promoting employee mindfulness. The objective of this systematic literature review is to gather and condense numerous prior research papers, offering a thorough summary of the existing data regarding the impact of leaders' transparency and self-awareness on promoting employees mindfulness. The systematic literature review approach is employed to offer a complete and unbiased overview of the current body of research pertaining to a certain subject matter. The process of identifying, analysing, and synthesising prior works is beneficial in addressing a particular research inquiry. The results indicate a noteworthy beneficial relationship between the level of leaders’ transparency and self-awareness and the extent of employees’ mindfulness. The prioritisation of fostering mindfulness practises among employees is crucial. The integration of mindfulness approaches has promise for augmenting a capacity to concentrate, participate in rational decision-making and proficiently cope with stress, so enhancing overall efficacy of employees within a professional context.